Effect of Differently Localised Electrical Stimulation and Therapeutic Exercises on Pain, Functional Status and Quality of Life in Subjects After Anterior Cruciate Ligament Reconstruction Surgery - Ernestas Rutkauskas; Saulė Sipavičienė; Vilius Baikštis; Petras Mikučionis (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Electrical stimulation is an effective treatment for restoring muscle strength in the thigh after anterior cruciate ligament reconstructive surgery.